Trends in the Use of Long-Acting Injectable Antipsychotics in the Province of Manitoba, Canada. Issue 1 (January 2020) - Janzen, Donica; Bolton, James; Kuo, I fan; Leong, Christine; Alessi-Severini, Silvia
Abstract: Background: Long-acting injectable antipsychotics (LAIAs) have advantages over oral antipsychotics but are not widely used. We aimed to evaluate the impact of market entry of second-generation LAIAs on prescribing trends. Methods: We used administrative health databases to describe trends in LAIA use from 1995 to 2015 in the Canadian province of Manitoba. Age- and sex-specific incident and prevalent use were determined using prescription dispensation records for the entire population. We used interrupted time series analysis with Poisson regression to estimate change in LAIA use attributable to the market entry of the second-generation LAIA risperidone. Results: We observed 3380 prevalent LAIA users and 2375 incident users in our cohort. Long-acting injectable antipsychotic use was higher in males. Incidence proportions declined from 21.5 users per 100, 000 in 1996 to 4.8 in 2004 and then climbed to 14.7 by 2015. First-generation LAIA use peaked at 94.6 prevalent users per 100, 000 in 1998 but fell to 40.9 in 2015. Long-acting injectable antipsychotic use increased 1.4% per quarter after the market entry of risperidone long-acting injectable. Conclusions: Risperidone risperidone long-acting injectable market entry had a positive impact on LAIA prescribing.